Evaluating the effect of enzymatic pretreatment on the anaerobic digestibility of pulp and paper biosludge - Bonilla, Sofia; Choolaei, Zahra; Meyer, Torsten; Edwards, Elizabeth A; Yakunin, Alexander F; Allen, D Grant (Biotechnology Reports, 2018)
Anaerobic digestion of biosludge has not yet been implemented in pulp mills due to low biogas yields. Enzymatic pretreatment of biosludge has shown improvements in biogas yields but results are varied. A key limitation of previous studies is that they fail to consider the COD contribution from the enzyme solutions. The aim of this study was to systematically investigate the potential for enzymatic pretreatment on the anaerobic digestibility of pulp mill biosludge. Out of the six enzymes tested, four enhanced the anaerobic digestibility of biosludge. At the end of the BMP, a maximum improvement of 26% in biogas yield was observed with protease from B. licheniformis. There was no correlation between enzymatic activities on standard substrates and/or on biosludge and the effect of enzymes on biogas yields. Enzymes have potential for improving biosludge anaerobic digestibility but more research on optimal conditions and potential synergies with other pretreatment is needed. This work was part of the research program on “Increasing Energy and Chemical Recovery Efficiency in the Kraft Process”, jointly supported by the Natural Sciences and Engineering Research Council of Canada (NSERC) (CRDPJ 428559-11) and a consortium of the following companies: Andritz, AV Nackawic, Babcock & Wilcox, Boise, Carter Holt Harvey, Celulose Nipo-Brasileira, Clyde-Bergemann, DMI Peace River Pulp, Eldorado, ERCO Worldwide, Fibria, FP Innovations, International Paper, Irving Pulp & Paper, Kiln Flame Systems, Klabin, MeadWestvaco, StoraEnso Research, Suzano, Tembec, Tolko Industries and Valmet.